The Impacts of Covid-19 on Management and Discussion Analysis (MD & A) Disclosures: Evidence in Malaysia - Nurul Nazlia Jamil; Azreen Jihan Che Mohd Hashim (Human Resource Management Academic Research Society, 2024)
As the Coronavirus (COVID-19) pandemic is predicted to plunge the global economy, the disclosure on the trends or uncertainties impacting the business operation and financial condition is deemed essential. One of the disclosure areas affected by COVID-19 is management discussion and analysis (MD&A) which is urged to report current and potential future impact of the global pandemic to operations and financial conditions. In this paper, the study is to analyse the information of MD&A disclosure whether the management stating their reaction in relation to COVID-19 implications. The quantitative methodology using secondary data has been utilized to conduct the study. Using a sample of 76 Malaysian public listed companies that made early disclosure on COVID-19 statement, the study employed sentiment analysis to code for the overall tone or sentiment statement made by the chairman/CEO in MD&A. The finding shows that 40.8% (n = 31 firms) of the top management signals pessimistic reaction (P), 21.1% (n =16 firms) shows optimistic reaction (O), 17% (n = 13 firms) shows realism reaction (R) and 21.1% (n = 16 firms) provides no statement on COVID-19 in their MD&A. The top management’s reaction could serve as one of the communication mediums to signal positive, neutral or negative financial and economic anticipation. We believe the study is timely to provide such evidence as capital market regulators worldwide recently has called for the stock exchange operator to issue additional guidance for companies going forward to inform their shareholders and the investing public about the impacts of the COVID-19 pandemic. Further researches can be conducted to analyse any action taken by companies to modify their MD&A disclosures to adequately capture all the elements of this developing situation and provide more information to users.